A SHORT OUTLINE OF THE TUNNEL OXIDES - Pasero M. (My University, 2005)
Within the large and comprehensive group of oxide minerals, the most relevant subgroup in the frame of microporous materials is that of the so-called “tunnel oxides.” This rather generic term historically refers to a number of minerals which, from a chemical point of view, are (mainly) manganese oxides. In nature manganese occurs in three different oxidation states—Mn2+, Mn3+ and Mn4+—with the latter being the dominant form in tunnel oxides.
Keywords: tunnel oxides